A3.07 How well do acpa discriminate and predict ra in the general population -– a study based on 12, 590 population-representative swedish twins. (24th February 2016) - Hensvold, AH; Frisell, T; Magnusson, PKE; Holmdahl, R; Askling, J; Catrina, AI
Abstract : Background and Objective: Anti citrullinated protein antibodies (ACPA) are highly specific for rheumatoid arthritis (RA), but the diagnostic accuracy of ACPA in the general population has not been thoroughly assessed. We aimed to assess the diagnostic accuracy of ACPAfor RA in the general population and to further characterise the ACPA repertoires. Material and Methods: Serum samples from alarge population-representative twin cohort consisting of 12, 590 individuals were analyzedfor the presence of ACPA using anti-CCP2 ELISA. All ACPA-positive samples (n = 350) were further tested on ELISAs for four peptide-specific ACPAs (alpha-enolase: aa5–21; collagen type II: aa359–369; fibrinogen: aa563–583 and vimentin: aa60–75). RA cases were identified by linkage to the Swedish National Patient Register at inclusion and after a median follow up of 37 months (IQR 31–49). Results: Three hundred fifty out of 12590 individuals had a positive anti-CCP2 test, measuring ACPA. Of these, 103 had an RA diagnosis at the time of blood donation and inclusion. During a median follow-up of 3 years, an additional 21 of the remaining 247 ACPA-positive individuals developed RA. Overall, anti-CCP2 test and high titers (>3x cut off) of anti-CCP2had sensitivity of 66%and 62% respectively (specificity of 98% and 99% respectively) for prevalent RA. Anti-CCP2 test had a positive predictive value of 29% for prevalent RA at inclusion (negative predictive value of 99.6%) in this population-representative cohort. High titers (>3x cut off) of anti-CCP2 increased the positive predictive value to 48% (negative predictive value of 99.5%). ACPA-positive individuals without RA had lower anti-CCP2 titers and fewer peptide-specific ACPAs than ACPA-positive patients with RA, and higher C-reactive protein levels than anti-CCP2-negative individuals without RA. Conclusions: Presence of ACPA and especially high titers of anti-CCP2 have a high diagnostic accuracy for an RA diagnosis in a population setting.